Acylcarnitines as markers of exercise‐associated fuel partitioning, xenometabolism, and potential signals to muscle afferent neurons. Issue 1 (12th December 2016) - Zhang, Jie; Light, Alan R.; Hoppel, Charles L.; Campbell, Caitlin; Chandler, Carol J.; Burnett, Dustin J.; Souza, Elaine C.; Casazza, Gretchen A.; Hughen, Ronald W.; Keim, Nancy L.; Newman, John W.; Hunter, Gary R.; et al.
Abstract : New Findings: What is the central question of this study? Does improved metabolic health and insulin sensitivity following a weight‐loss and fitness intervention in sedentary, obese women alter exercise‐associated fuel metabolism and incomplete mitochondrial fatty acid oxidation (FAO), as tracked by blood acylcarnitine patterns? What is the main finding and its importance? Despite improved fitness and blood sugar control, indices of incomplete mitochondrial FAO increased in a similar manner in response to a fixed load acute exercise bout; this indicates that intramitochondrial muscle FAO is inherently inefficient and is tethered directly to ATP turnover. With insulin resistance or type 2 diabetes mellitus, mismatches between mitochondrial fatty acid fuel delivery and oxidative phosphorylation/tricarboxylic acid cycle activity may contribute to inordinate accumulation of short‐ or medium‐chain acylcarnitine fatty acid derivatives [markers of incomplete long‐chain fatty acid oxidation (FAO)]. We reasoned that incomplete FAO in muscle would be ameliorated concurrent with improved insulin sensitivity and fitness following a ∼14 week training and weight‐loss intervention in obese, sedentary, insulin‐resistant women. Contrary to this hypothesis, overnight‐fasted and exercise‐induced plasma C4–C14 acylcarnitines did not differ between pre‐ and postintervention phases. These metabolites all increased robustly with exercise (∼45% of pre‐intervention peak oxygen consumption) and decreased during a 20 min cool‐down. This supports the idea that, regardless of insulin sensitivity and fitness, intramitochondrial muscle β‐oxidation and attendant incomplete FAO are closely tethered to absolute ATP turnover rate. Acute exercise also led to branched‐chain amino acid acylcarnitine derivative patterns suggestive of rapid and transient diminution of branched‐chain amino acid flux through the mitochondrial branched‐chain ketoacid dehydrogenase complex. We confirmed our prior novel observation that a weight‐loss/fitness intervention alters plasma xenometabolites [i.e. cis ‐3, 4‐methylene‐heptanoylcarnitine and γ‐butyrobetaine (a co‐metabolite possibly derived in part from gut bacteria)], suggesting that host metabolic health regulated gut microbe metabolism. Finally, we considered whether acylcarnitine metabolites signal to muscle‐innervating afferents; palmitoylcarnitine at concentrations as low as 1–10 μm activated a subset (∼2.5–5%) of these neurons ex vivo . This supports the hypothesis that in addition to tracking exercise‐associated shifts in fuel metabolism, muscle acylcarnitines act as signals of exertion to short‐loop somatosensory–motor circuits or to the brain. Abstract :